2018
DOI: 10.7456/1080sse/156
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction of Learning Management System Usage in a Blended Learning Environment among Undergraduate Students

Abstract: Learning management system (LMS) helps higher learning institutions to manage their instructional resources and complement their traditional way of teaching. Although LMS survives via students' and instructors' use, its adoption is initiated by the students' satisfaction. Thus, the objectives of this study are to examine the level of LMS satisfaction among university students in a blended learning program and to investigate the factors that may impact their satisfaction. A quantitative research approach via a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…This result was confirmed by Ghazal et al (2018) study, which revealed that both students' perceived ease of using an alternative learning modality and its perceived usefulness had a significant positive relationship with student satisfaction. With this, HEIs need to consider the relationships between the factors of acceptance and joy in implementing a modular learning modality.…”
Section: Correlation Between the Students' Evaluation And Satisfactio...supporting
confidence: 53%
“…This result was confirmed by Ghazal et al (2018) study, which revealed that both students' perceived ease of using an alternative learning modality and its perceived usefulness had a significant positive relationship with student satisfaction. With this, HEIs need to consider the relationships between the factors of acceptance and joy in implementing a modular learning modality.…”
Section: Correlation Between the Students' Evaluation And Satisfactio...supporting
confidence: 53%
“…As technology adoption advances, students might find it easier to adapt to the learning process. Ghazal et al (2018) stated that there was a significant relationship between technology acceptance and learner satisfaction with regard to the use of learning environments. The temporal and spatial autonomy advantages of e-learning also positively affected learners' perception of acceptance and satisfaction (Al-Hawari & Mouakket, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Student satisfaction was favorably influenced by students' perceptions of the online learning environment as being useful, or favorable in terms of efficiency. Various studies found perceived usefulness to be an important predictor of learner satisfaction in the e-learning environment (Ghazal et al, 2018;Jo et al, 2018;Lwoga, 2016;Park & Kim, 2012;Saxena et al, 2021). As the system's functionality grows, so would the learners' productivity, learning performance, and control over the system and the learning process, all of which contribute indirectly to learning satisfaction (Lwoga, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Research on satisfaction in online learning has recently focused on several specific areas. For example, some researchers explored undergraduate students' satisfaction with utilizing learning management systems in a blended learning setting [30]. Liu [31] investigated strategies to enhance satisfaction among Chinese college students in the context of online English teaching.…”
Section: Literature Reviewmentioning
confidence: 99%